Lifestyle factors and prevalence of semen abnormalities among men undergoing infertility evaluation at oak specialist hospital: A retrospective cohort study - Rex Mawuli Kwadjo Djokoto; Victor Boachie Owusu; Edward Anabila Agana; Kingsley Afreh Nduroh; Johnny Arthur-Komeh; Opei Adarkwa; Andrew Panyin Vormawor; Anthony Amanfo Ofori; Isaac Kofi Adu (PLoS ONE, 2026)
Background Male infertility constitutes a notable health burden in Sub-Saharan Africa, contributing to approximately 40–50% of all infertility cases, compounded by cultural stigma and a grave knowledge issue. The study aimed to apply the updated World Health Organisation (WHO) 6th Edition (2021) criteria to a Ghanaian cohort, generating contemporary prevalence data on semen abnormalities. Methods A retrospective cohort study design was employed, analysing the medical and laboratory records of 221 men who underwent semen analysis as part of an infertility investigation at Oak Specialist Hospital, Kumasi, Ghana. A consecutive sampling method was used to include all eligible patient records from September 1, 2022, to August 31, 2024. Key variables included semen parameters (volume, concentration, motility, morphology, leukocytes) analysed per WHO 2021 guidelines, and associated lifestyle and demographic factors. Data were analysed using descriptive statistics, prevalence rates, and regression analysis. Results The study identified high prevalence rates of oligozoospermia (38.91%) and teratozoospermia (38.46%). A critically high prevalence of leukocytospermia was the most striking finding, affecting 80.54% of the cohort. Regression analysis revealed significant negative associations between sugary drink consumption and sperm motility (p = 0.038) and a positive association between caffeine intake and sperm morphology (p = 0.011). Paradoxically, the cohort’s median values for semen volume, concentration, and motility were significantly above the WHO 2021 lower reference limits. Conclusion Using current international standards, this study provides updated baseline data on male infertility patterns in urban Ghana. The findings reveal a high burden of specific abnormalities, particularly in sperm morphology and leukocyte concentration, which may be more clinically relevant than simple concentration or motility deficits in this population. Modifiable lifestyle factors, such as diet, represent viable targets for public health intervention. These results are vital for clinical benchmarking, guiding targeted health strategies, and establishing a foundation for future comparative studies in similar resource-constrained settings.